Divorce in China : institutional constraints and gendered outcomes - He, Xin (Professor of law) (New York University Press, 2021)
"Despite the increase of gender consciousness in Chinese society and a trove of legislation to protect women, why are Chinese women still disadvantaged in divorce courts? Xin He argues that institutional constraints to which judges are subject, a factor largely ignored by existing literature, play a crucial role. Twisting the divorce law practices are the bureaucratic incentives of courts and their political concerns for social stability. Because of these concerns, judges often choose the most efficient, and safest, way to handle issues in divorce cases. In so doing, they allow the forces of inequality in social, economic, cultural, and political areas to infiltrate their decisions. Divorce requests are delayed; domestic violence is trivialized; and women's child custody is sacrificed. The institutional failure to enforce the laws has become a major obstacle to gender justice. Divorce in China is the only study of Chinese divorce cases based on fieldwork and interviews conducted inside Chinese courtrooms over the course of a decade"--